P74 Rituximab effect on B cell depletion in paediatric patients with autoimmune diseases: a retrospective dose-response analysis of an observational study. Issue 6 (17th May 2019) - Pan, S; Yu, H; Surti, A; Cheng, I; Marks, SD; Brogan, PA; Eleftheriou, D; Standing, JF
Abstract : Background: Rituximab is a chimeric IgG1 monoclonal antibody that depletes B cells for the treatment of several conditions including autoimmune diseases. It is not licensed for use in children but administered off-label. This study aimed to quantify the effect of rituximab on B cell depletion in children with autoimmune diseases and to optimise the dosing regimen. Methods: Electronic health record data were collected from a retrospective and anonymised study at Great Ormond Street Hospital in London. Dosing protocols of rituximab were two 750 mg/m 2 intravenous infusions or four weekly 375 mg/m 2 infusions. Serum concentrations of rituximab were not measured. CD19+ lymphocyte counts were taken before and after rituximab treatment. A turnover mechanism described the life cycle of CD19+ lymphocytes with rituximab increasing the death rate of CD19+ lymphocytes; a negative feedback was added on the production rate to examine the rebound effect. Rituximab was assumed to decay by first-order kinetics. Results: 258 measurements of CD19+ lymphocyte counts were collected from 39 children with 8 autoimmune diseases. The dose-response model well described the time course of CD19+ lymphocytes following rituximab administration. The elimination half-lives of rituximab and CD19+ lymphocytes were estimated to be 19 and 35 days, respectively, consistent with findings from other studies [1–5]. The rebound increase in CD19+ lymphocytes was found negligible. Methotrexate and cyclophosphamide increased the maximum death rate by 66% and 38% respectively. Age and gender were not significant covariates. Simulations from the model suggested that a single infusion of rituximab of 375 mg/m 2 can provide similar six-month suppression of CD19+ lymphocytes to the higher doses currently used. Methotrexate or cyclophosphamide added minimal suppression effect on CD19+ lymphocytes when taken concurrently with rituximab. Conclusions: Our results could be used in future to assess the effect of rituximab biosimilars and to inform biosimilar dosing in paediatric populations. References: Ng, et al. J Clin Pharmacol . 2005; 45:792–801 Li, et al. Blood . 2007; 110:2371 Li, et al. J Clin Pharmacol . 2012; 52:1918–26 Fulcher and Basten. Immunol Cell Biol . 1997; 75:446–55 Macallan, et al. Blood . 2005; 105:3633–40 Disclosure(s): Nothing to disclose